Clutch size in the small-sized lizard Eurolophosaurus nanuzae (Tropiduridae): does it vary along the geographic distribution of the species? - Conrado A. B Galdino; Monique Van Sluys (Iheringia: Série Zoologia, 2011)
We studied life history traits of females of the lizard Eurolophosaurus nanuzae (Rodrigues, 1981), an endemic species of rock outcrop habitats in southeastern Brazil. During October 2002 and 2003 we sampled three populations in sites that encompass the meridional portion of the geographic range of the species. Clutch size varied from one to three eggs, with most females carrying two eggs. Clutch size did not vary among populations, but was correlated to female body size. Only larger females produced clutches of three eggs. Females of the small-sized E. nanuzae produce eggs as large as those of medium-sized tropidurids, thus investing a considerable amount of energy to produce clutches resulting in high values of relative clutch mass.